LANGUAGE POLICY AND SCHOOL EDUCATION AS MAIN FACTORS OF UKRAINE STATE CREATION - Malykhin, Oleksandr; Aristova, Nataliia; Dichek, Nataliia; Zahorulko, Maryna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
The authors present their views on the formation of the Language Policy and the role of general secondary school education as important factors in the Ukraine state creation shortly before and in the first years of Ukraine’s independence. The main drivers of changes in the Language Policy of the Soviet government regarding the state of the Ukrainian language in the USSR are identified. These drivers of changes include (1) activities of nationally oriented public organisations, primarily Ukrainian writers, historians, human rights defenders, and the Ukrainian language admirers; (2) public desire to develop nationally oriented education, which forced the authorities to start implementing very specific measures, first of all – in the field of general secondary school education; (3) the gradual formation of a scientific and pedagogical basis for the versatile Ukrainisation and humanisation of education and upbringing of children and youth giving priority to their native language as a language of instruction; (4) the need to introduce measures for external and internal differentiation of general secondary school education;(5) the psychologisation of the educational process. Based on documentary sources, it is argued that general secondary school education played the role of an important factor in the Ukraine state creation which was facilitated by the specific measures developed by the Ministry of Education of Ukraine to implement the Ukrainian idea in school practice in the first years of independence. The novelty of the present research is that authors extrapolate the past educational experience to the current language situation in general secondary school education in Ukraine. Moreover, the authors represent the opinions of contemporary Ukrainian sociolinguists on the state Language Policy in the field of general secondary school education. The research proves that the strategic ideas laid down at the turn of the last decades of the last century regarding the Educational Policy of independent Ukraine in the field of general secondary school education played an important role in improving the position of the Ukrainian language and in shaping Ukrainian self-identity among children and young people which explicitly and implicitly reinforced the key strategic idea – the idea of the Ukrainian State creation.